Current status of different detector technology in the searches of dark matter events. Issue 1 (June 2021) - Karmakar, S.; Singh, M. K.; Singh, V.
Abstract: In this article, we review the possible candidates of dark matter and their proposed properties. We have focused on different methods used for the detection of the dark matter candidates such as, search of WIMPs at the accelerators, indirect and direct detection of WIMPs. We have highlighted the different detector technologies such as, charge collection after ionization, bubble formation in superheated liquid by charge particle, scintillation produced due to the incident radiation, cryogenic detection technique, noble liquid as detector material, time projection chamber, which are used by different experimental collaborations worldwide.